Adhesion strength of a living cell to various substrates measured using a cup-attached atomic force microscopy chip. (6th December 2017) - Kim, Hyonchol; Ishibashi, Kenta; Matsuo, Kosuke; Kira, Atsushi; Onomura, Yui; Okada, Tomoko; Nakamura, Chikashi
Abstract: Cell adhesion strengths to various substrates were quantitatively measured using atomic force microscopy (AFM). A cup-shaped metal hemisphere was attached to the apex of the AFM cantilever, the "cup-chip" approached a cell (FP10SC2) to pick it up, the captured cell approached any one of six different substrates [gold (Au), nickel (Ni), bovine serum albumin (BSA), an amino group (NH2 ), poly(tetrafluoroethylene) (PTFE), and structured PTFE (sPTFE)], and the cell adhesion strength at the initial contact period was evaluated by detaching the cell from the substrate. The results obtained showed that the force needed to detach the cell from the NH2 substrate was more than 3-fold larger than that of metal substrates (Au and Ni), more than 15-fold larger than that of biochemically treated substrates (BSA), and more than 20-fold larger than that of hydrophobic substrates (PTFE and sPTFE). Using differences in adhesion strengths, a cell on a sPTFE substrate was picked up using a BSA-coated cup-chip, placed on a NH2 substrate, repeating this cell manipulation five times, and line patterning of cells was achieved. These results indicate that measurements of cell adhesion strength are fundamental to fabricate desired cell networks and the cup-chip is a useful tool for achieving easy cell manipulation.